PERAN GURU PENDIDIKAN AGAMA ISLAM SEBAGAI AGEN PERUBAHAN DALAM MEMBENTUK KARAKTER SOPAN SANTUN SISWA BROKEN HOME DI SMP AKHLAKUL KARIMAH SEBUBUS PALOH - Tasya Ramadani; Dewi Ferawati; Meriyanti Meriyanti (CV. Adiba Aisha Amira, 2025)
This study explores the strategic role of Islamic Education (PAI) teachers as agents of change in shaping the polite character of students from broken home families at SMP Islam Akhlakul Karimah Sebubus Paloh. The research arises from the phenomenon of declining manners and discipline among students experiencing family dysfunction, which affects their emotional, social, and academic development. The objectives of this study are to describe: (1) the behavioral characteristics of broken home students in the school environment, (2) the role of Islamic Education teachers as agents of change in fostering polite behavior, and (3) the implications of character building through Islamic values on students’ conduct. This research employed a qualitative approach with a phenomenological design. Data were collected through interviews, observations, and documentation, and analyzed using data condensation, data presentation, and conclusion drawing with verification. The validity of the data was tested through source triangulation, technical triangulation, and member checking. The results show that broken home students tend to experience emotional instability, low self-confidence, and difficulty in social interactions. However, through the roles of Islamic Education teachers as educators, mentors, role models, and motivators, students can be guided to develop courteous and respectful behavior. Character building efforts are carried out through exemplary actions, habituation, advice, and personal approaches grounded in Islamic values. This study emphasizes that Islamic Education teachers play a crucial role in internalizing moral and spiritual values to build noble character among students, even those from non-intact family backgrounds.